The Correlation Between Surfactant Protein-D (SP-D) Serum Level and Intubation Time on Covid-19 Patients in Indonesia - Arinald Findari Manoppo, -
Abstract : COVID-19 patients with ARDS who are admitted to the ICU needed tracheal intubation and mechanical ventilation, where the tracheal intubation strategy as early as possible with the good protocol ventilation management produce favorable patient outcomes. In performing the intubation needed to consider the right time to produce optimum outcome. The increase of Surfactant Protein-D serum level is a specific indicator of lung injury with severe ARDS and the duration of intubation. From that, the aims of this study to determine the correlation between Surfactant Protein-D (SP-D) and intubation time on COVID-19 patients. This observational analytic research with retrospective cohort design is conducted during March-August period and has obtained the ethics certificate from the Ethical Committee of Dr. Soetomo Surabaya. The examination of Surfactant Protein-D level is conducted on patients who have met the inclusion and exclusion criteria and the intubation time is recorded. In this research obtained 28 patients, where 20 patients are male and 8 patients are female. The comorbid factor that most affect the patient’s condition is Diabetes Mellitus. The average of Surfactant Protein-D serum level is 42,15 ng/ml (SD ± 32,71 ng/ml). The statistics analysis results showed that there is no meaningful correlation between Surfactant Protein-D serum level and intubation time (p: 0,304). In addition, it is also found that the SP-D level results which has no meaningful difference in the group of patients who died and survived (p: 0,159). The examination of Surfactant Protein-D level did not show a meaningful correlation with intubation time on Covid-19 patients.